Strategi Pemasaran Melalui Media Sosial, Citra Toko Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Kasus Pelanggan Meteor Cell Malang) - Hanif, Fanny Purama; Asiyah, Siti; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Business people are impacted by the rapid development of information technology, which helps them become famous all over the world. By using social media platforms such as Instagram and Tiktok, shops can promote and introduce the products they sell using the shop image, which is the public's view or perception of the shop's name or products in terms of value, quality and price. However, service quality is the level of excellence that is expected to fulfill consumers' desires for the services provided by the brand to them. Social media marketing, store image, and service quality related to customer satisfaction are the objectives of this research. The research method used is quantitative with a purposive sampling research method. In this research, 93 Meteor Cell Malang customers were sampled. In this research, a data collection method using a survey was used. To analyze the data, SPSS 23 was used. This includes instrument testing, normality testing, classical assumptions, multiple linear testing, hypothesis testing, and coefficient of determination testing. research show that social media, store image and service quality have a significant simultaneous effect on Meteor Cell Malang customer satisfaction. Furthermore, partially, social media, store image and service quality have a positive and significant effect on customer satisfaction at Meteor Cell Malang. Keywords: Media Sosial, Citra Toko, Kualitas Pelayanan, Kepuasan Pelanggan Meteor Cell Malang